2017
DOI: 10.18203/2394-6040.ijcmph20172170
|View full text |Cite
|
Sign up to set email alerts
|

Socio demographic and clinical profile of dengue fever cases at a tertiary care hospital, Hyderabad, Telangana

Abstract: Background: Dengue fever is caused by Dengue Virus, belonging to the family Flaviviridae, transmitted by Aedes aegypti and Aedes albopictus mosquito. There are four distinct dengue virus serotypes (DEN-1, DEN-2, DEN-3, and DEN-4). This viral disease of humans has become a major international public health concern in recent years. Differential diagnosis based on symptoms is challenging due to dengue’s non-specific symptoms such as fever, aches and fatigue that are often overlap with other endemic infections. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Chajhlana SPS et al ( 17 ) and Dutta et al ( 18 ) had shown that more males were affected similar to the findings of the present study. In a study conducted by Balasubramaniam et al ( 19 ), fever was the most common symptom observed similar to the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Chajhlana SPS et al ( 17 ) and Dutta et al ( 18 ) had shown that more males were affected similar to the findings of the present study. In a study conducted by Balasubramaniam et al ( 19 ), fever was the most common symptom observed similar to the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Most dengue patients detected during this study were males (68.6%), although male patients were also more likely to be enrolled in the study (69.3%). This difference likely arose from unequal health care utilization among male and female patients, which is a typical feature in South Asia 23 . The proportion of male febrile patients (38.52%), who were positive for dengue was similar to that of female febrile patients (39.85%), with the difference not being statistically significant (P > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…also P P Vazhayil et al, K Jayasree et al and Shubhankar Mishra et al and Anand et alstudies. 4,[6][7][8][9][10] In the present study most commonly affected age group is 6-10 years of age 95 cases (47.9%)(Table-2). K Jayasree et al study shows 6-10 yrs.…”
Section: Discussionmentioning
confidence: 83%
“…Study conducted by Anand et al found 83.3% positive cases. 4,5 Majority of cases are males 62% and 38% were females (Figure 1). Chajhlana SPS et al and Tabassum et al in their study found that there was more number of males.…”
Section: Discussionmentioning
confidence: 99%